Mammary like gland adenoma with GATA-3 expression - a benign vulval tumor with mammary differentiation often misdiagnosed as adenocarcinoma - Deval Parekh; Sunaina Wadhwa; Asima Mukhopadhyay; Angad Singh (New Indian Journal of OBGYN, 2021)
Papillary hidradenoma/ mammary-like gland adenoma (MLGA) is a benign glandular tumor of the vulva. It presents as a mass lesion which often undergoes secondary ulceration and bleeding resembling a malignant tumor. It arises from specialized anogenital glands in the labial folds which resemble mammary glands on microscopy. The tumour shows a tubulo-papillary architecture and is composed of bland columnar cells with apical snouting. GATA-3 is a transcription factor and it’s expression is essential for normal mammary gland development. GATA-3 immunohistochemistry (IHC) is positive in luminal cells of breast and its positive in ductal hyperplasia as well as in breast carcinoma. In summary, we describe a case of a benign vulval mammary gland like adenoma with diffuse GATA-3 expression which was originally diagnosed as a malignant low-grade polymorphous adenocarcinoma and discuss its clinical and associated histopathological findings.